2007
DOI: 10.1007/s11517-007-0237-3
|View full text |Cite
|
Sign up to set email alerts
|

Temporal evolution of mechanical properties of skeletal tissue regeneration in rabbits: an experimental study

Abstract: Various mathematical models represent the effects of local mechanical environment on the regulation of skeletal regeneration. Their relevance relies on an accurate description of the evolving mechanical properties of the regenerating tissue. The object of this study was to develop an experimental model which made it possible to characterize the temporal evolution of the structural and mechanical properties during unloaded enchondral osteogenesis in the New Zealand rabbit, a standard animal model for studies of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…The overall geometry of the regenerated segment is thus still evolving [16]. This is in good agreement with the histology analysis which showed a massive cellular proliferation.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The overall geometry of the regenerated segment is thus still evolving [16]. This is in good agreement with the histology analysis which showed a massive cellular proliferation.…”
Section: Discussionsupporting
confidence: 87%
“…A first in-vivo study based on periosteal properties demonstrated that it is possible to regenerate a whole bone volume after a large segmental resection in the New-Zealand rabbit [16]. Moukoko [16] produced regenerated osteocular material under almost nought mechanical load, analyzing the time sequences of the regeneration process.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Isaksson et al (2009) have shown that although the sequential order of events in the predicted healing process is not significantly influenced by the chosen material properties, the amount of bone formation and mechanical stability at different stages of the healing process and the time to healing were significantly affected by the permeability of granulation tissue, the Young's modulus of cartilage and permeability of immature bone, and therefore adequate characterization of these material properties is important when using models to design new experiments. Moukoko et al (2007) developed a rabbit model to characterize the temporal evolution of the structural and mechanical properties of the developing tissues during unloaded endochondral osteogenesis. Some recent studies have looked into other aspects of the higher mentioned uncertainties.…”
Section: Modeling Framework Assumptions Validation and Sensitivitymentioning
confidence: 99%